2010
DOI: 10.1051/epjconf/20100203002
|View full text |Cite
|
Sign up to set email alerts
|

Photon Strength Functions at the Low-Energy Tail of GEDR

Abstract: Abstract. It is demonstrated that available experimental information on photon strength functions (PSFs) at energies below about 10 MeV is far from desired. Problems that occur during the extraction of PSFs from (n,γ), (γ,γ'), and 3 He-induced reactions are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…[46], the efficiency corrected ELBE experimental spectra seem to be reasonably consistent with γ-ray spectra coming directly from dicebox simulations with no pygmy dipole resonance, i.e., a resonance structure in f E1 at E γ ≈ 6 MeV. This finding might indicate that the "iterative" method used in Ref.…”
Section: Conclusion On Psfs In 98 Mosupporting
confidence: 73%
“…[46], the efficiency corrected ELBE experimental spectra seem to be reasonably consistent with γ-ray spectra coming directly from dicebox simulations with no pygmy dipole resonance, i.e., a resonance structure in f E1 at E γ ≈ 6 MeV. This finding might indicate that the "iterative" method used in Ref.…”
Section: Conclusion On Psfs In 98 Mosupporting
confidence: 73%
“…Neutron-capture experiments often have indicated an overshoot of the Lorentzian over the observed E1 strength at the low-energy tail of the GDR. 100,156,157,158 On the basis of these data theoretical explanations have been proposed to explain the differences. 100,159,160,158 smooth Lorentzian was found consistently and denoted as pygmy dipole resonance (PDR).…”
Section: Electromagnetic Transitionsmentioning
confidence: 99%
“…158 Recent investigations have shown that the E1 strength can be described by Lorentzians for a large range of nuclei 162,163,164. It was also shown that indirect determinations of PDFs are prone to large uncertainties due to the experimental difficulties and some claims of enhancement165,166 at low E γ have been premature.100,158,167,168 However, in some nuclei extra strength at low energy with respect to the The Path to Improved Reaction Rates for Astrophysics 65…”
mentioning
confidence: 99%
“…The situation below or near the particle separation threshold is illustrated in Figure 2 for 98 Mo [7]: one can see the discrepant results from the different experimental methods used to determine PSFs.…”
Section: Below or Near Particle Thresholdmentioning
confidence: 99%